Socio-Economic Status and Inequalities in Children's IQ and Economic Preferences - Thomas Deckers; Armin Falk; Fabian Kosse; Pia Pinger; Hannah Schildberg-Hörisch (Institute of Labor Economics (IZA), 2017)
This paper explores inequalities in IQ and economic preferences between children from high and low socio-economic status (SES) families. We document that children from high SES families are more intelligent, patient and altruistic, as well as less risk-seeking. To understand the underlying causes and mechanisms, we propose a framework of how parental investments as well as maternal IQ and economic preferences influence a child's IQ and preferences. Within this framework, we allow SES to influence both the level of parental time and parenting style investments, as well as the productivity of the investment process. Our results indicate that disparities in the level of parental investments hold substantial importance for SES gaps in economic preferences and, to a lesser extent, IQ. In light of the importance of IQ and preferences for behaviors and outcomes, our findings offer an explanation for social immobility.
Keywords: C90; D64; D90; D81; J13; J24; J62; 330; socio-economic status; time preferences; risk preferences; altruism; experiments with children; origins of preferences; human capital